Nursing students’ quality of life - Fidecki, Wiesław Marian; Wysokiński, Mariusz; Jakubiec, Izabela; Kulina, Dorota; Kuszplak, Kamil (Journal of Education, Health and Sport, 2018)
Introduction Quality of life is a broad notion comprised of: a human being’s health state, their psychological state, social relations, a degree of independence as well as their attitude toward their surroundings. The aim of the study The research aimed at specifying nursing students’ subjective quality of life. Material and methods The study involved 210 nursing students of the Medical University of Lublin. The research cohort was comprised of 199 females and 11 males. The investigation was administered by means of the Polish version of the WHOQOL-Bref scale. This tool allowed to specify the quality of life in physical, psychological, environmental and social domains. Results Investigated students’ quality of life averaged out at 3.98, whereas their health state self-assessment averaged out at 3.73. The physical domain scored highest (averagely 15.54). Lower values were obtained in the sphere of social relations (15.52) and the environmental domain (13.81). The psychological domain scored lowest (13.62). Conclusions Nursing students’ quality of life averaged out at a satisfactory level. Investigated students’ health state self-assessment and marital status made a considerable difference for their quality of life. Male students and those with urban background assessed their quality of life at relatively higher levels.